Thống kê hoạt động chất vấn tại kỳ họp Quốc hội, phiên họp UBTVQH nhiệm kỳ khóa XV - Quốc hội Khoá XV (2023)
Toàn văn Thống kê hoạt động chất vấn tại kỳ họp Quốc hội, phiên họp UBTVQH nhiệm kỳ khóa XV.